ОПТИМІЗАЦІЯ ГРАФІКІВ ЕЛЕКТРИЧНОГО НАВАНТАЖЕННЯ АГРЕГАТОРОМ В ЛОКАЛЬНИХ ЕЛЕКТРОЕНЕРГЕТИЧНИХ СИСТЕМАХ - Бєлоха, Г.С.; Сичова, В.В. (Інститут електродинаміки Національної академії наук України, 2023)
The market operation of the electricity distribution system has gained significant expansion due to the growing use of renewable and distributed sources. This paper presents strategies for optimizing load schedules by aggregators of local systems. Optimization of load schedules is to minimize the total costs of the supplier to reduce the cost of electricity and lower prices for the consumer. In local systems, which include diesel generators, the main component that most affects the price per 1 kW is the consumption of primary fuel of diesel generators. The objective function proposed in this study minimizes the supplier's primary fuel consumption by optimally redistributing power to each generator. The basic load schedule and application of schedule optimization strategies were studied: load reduction, load transfer, increase of minimum loads, flexible load change. When using the optimal algorithm, the costs are 5-6% relative to the uniform power distribution.